LE CONCEPT DE TRANSCENDANCE CHEZ GABRIEL MARCEL ET PIERRE BOUTANG - MERCIER, Paul (Studia Universitatis Babeș-Bolyai Philosophia, 2018)
The concept of Transcendence in Gabriel Marcel and Pierre Boutang. This article intends to explore the concept of Transcendence in Gabriel Marcel and Pierre Boutang’s writings. In philosophy, Transcendence is usually seen as a kind of sphere that creates a contact between humankind and divinity, or as surpassing oneself. Contrariwise, Gabriel Marcel and Pierre Boutang show that transcendence draws a path that the Christian viator – a notion explained throughout this article – has to take using the concepts of Mystery with Gabriel Marcel and Secret with Pierre Boutang, in order to achieve salvation.